Experience with invasive and non-invasive sensors for anaesthesia - Rolfe, P (Acta anaesthesiologica Scandinavica. Supplementum, 1995)
This paper reviews experiences with the development and clinical use of invasive and non-invasive sensors for continuous real-time monitoring. The clinical focus, and inspiration, for this work has been the fetus and the newborn baby, but the work described is also directly relevant to the challenges of performing timely assessments of blood gas and acid-base status in subjects undergoing anaesthesia and critical care. The first results obtained from the use of invasive PO2, PCO2, and pH sensors in humans, in the late 1960's, provided exciting new insights in to basic physiological processes, but the sensors were very limited in their performance, particularly with regard to haemocompatibility. Research since that time has been concerned with attempting to overcome the problems of blood interactions with sensor surfaces, and an approach based on the mimicry of cell membrane phospholipid biochemistry is described here. The issue of haemocompatibility may be obviated by the utilisation of non-invasive methods. The interrogation of tissues by near infra-red radiation (700-1000 nm) is described, with particular emphasis on the development of spectrophotometric techniques for the measurement of HHb, HbO2, and Hbtot in the brain. Prospects for the measurement of other species, such as glucose, and of achieving spatial discrimination within tissues are also considered.